The microtubule network enables Src kinase interaction with the Na,K-ATPase to generate Ca2+ flashes in smooth muscle cells - Rognant, Salomé; Kravtsova, Violetta V.; Bouzinova, Elena V.; Melnikova, Elizaveta V.; Krivoi, Igor I.; Pierre, Sandrine V.; Aalkjaer, Christian; Jepps, Thomas A.; Matchkov, Vladimir V. (Frontiers in Physiology, 2022)
Background: Several local Ca2+ events are characterized in smooth muscle cells. We have previously shown that an inhibitor of the Na,K-ATPase, ouabain induces spatially restricted intracellular Ca2+ transients near the plasma membrane, and suggested the importance of this signaling for regulation of intercellular coupling and smooth muscle cell contraction. The mechanism behind these Na,K-ATPase-dependent ‘Ca2+ flashes’ remains to be elucidated. In addition to its conventional ion transport function, the Na,K-ATPase is proposed to contribute to intracellular pathways, including Src kinase activation. The microtubule network is important for intracellular signaling, but its role in the Na,K-ATPase-Src kinase interaction is not known. We hypothesized the microtubule network was responsible for maintaining the Na,K-ATPase-Src kinase interaction, which enables Ca2+ flashes.. Methods: We characterized Ca2+ flashes in cultured smooth muscle cells, A7r5, and freshly isolated smooth muscle cells from rat mesenteric artery. Cells were loaded with Ca2+-sensitive fluorescent dyes, Calcium Green-1/AM and Fura Red/AM, for ratiometric measurements of intracellular Ca2+. The Na,K-ATPase α2 isoform was knocked down with siRNA and the microtubule network was disrupted with nocodazole. An involvement of the Src signaling was tested pharmacologically and with Western blot. Protein interactions were validated with proximity ligation assays. Results: The Ca2+ flashes were induced by micromolar concentrations of ouabain. Knockdown of the α2 isoform Na,K-ATPase abolished Ca2+ flashes, as did inhibition of tyrosine phosphorylation with genistein and PP2, and the inhibitor of the Na,K-ATPase-dependent Src activation, pNaKtide. Ouabain-induced Ca2+ flashes were associated with Src kinase activation by phosphorylation. The α2 isoform Na,K-ATPase and Src kinase colocalized in the cells. Disruption of microtubule with nocodazole inhibited Ca2+ flashes, reduced Na,K-ATPase/Src interaction and Src activation. Conclusion: We demonstrate that the Na,K-ATPase-dependent Ca2+ flashes in smooth muscle cells require an interaction between the α2 isoform Na, K-ATPase and Src kinase, which is maintained by the microtubule network.